Understanding CS1 Students; Defective Software. - Guzdial, Mark; Meyer, Bertrand (Communications of the ACM, 2012)
The Communications Web site, http://cacm.acm.org, features more than a dozen bloggers in the BLOG@CACM community. In each issue of Communications, we'll publish selected posts or excerpts. twitter ollow us on Twitter at http://twitter.com/blogCACM http://cacm.acm.org/blogs/blog-cacm Mark Guzdial writes about why teachers must grasp introductory CS students' theories about computing. Bertrand Meyer argues for the necessity of analyzing large-scale software disasters and publishing a detailed technical study.